A multi-dimensional framework for the development of authentic consumer products - Per Kristav; Izabelle Bäckström; Axel Nordin; Anders Warell; Olaf Diegel (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2018)
A common assumption in product value literature is that authenticity is what contemporary consumers value the most. However, as this paper illustrates, the meaning of authenticity is unclear, and the term appears foreign to product development practitioners. The purpose of this paper is to explore in what ways product development professionals talk about product value in general and how this relates to authenticity. The analysis of the interviews reveals that product developers must embrace authenticity as a holistic framework if the phenomenon is to be constructive for companies within the product development industry. In line with the concept of authenticity as a multi-dimensional framework, this paper suggests that authenticity does not solely result from certain intrinsic tangible or intangible product characteristics, and that commercially strong products and brands do not automatically become "authentic". The contribution of this paper to the product development field is a framework for a multi-dimensional construct of authenticity, and an account of what representatives within selected companies talk about when asked about how they create consumer value, and how they contribute to valuable consumer experiences. The findings are analysed and discussed in the context of literature on product development, brand management and marketing management.
Keywords: D47; M11; M31; 650; brand value; product value; product authenticity; brand authenticity; authentic design; consumer value